Peran Marketing Mix Dalam Membangun Citra Sekolah - Nada Afisa Ad’jen; Ira Nuriya Santi; Maskuri Sutomo; Erwan Sastrawan (Lembaga Pengembangan Kinerja Dosen, 2024)
The objective of this research is to understand the role of the marketing mix in shaping the school’s image. The research employs a qualitative descriptive method, involving school environment observation and interviews. From the research, it can be concluded that SDN 10 Pantoloan actively contributes to branding its school image. By delivering educational services with considerations from the marketing mix, SDN 10 Pantoloan can maintain its standards in creating a positive image. The school is able to showcase achievements, both academic and non-academic, provide better interaction with the community, and offer the necessary facilities to support a better school image